Developmentally moderated focus on form instruction and feedback in an Indonesian kindergarten EFL programme. Issue 2 (18th July 2022) - Kawaguchi, Satomi; Hardini, Isriani
Abstract : This study investigates the effect of developmentally moderated focus on form (DMFonF) instruction and feedback within processability theory (PT) on early grammatical development in an Indonesian kindergarten EFL programme, focusing on the acquisition of plural marking of nouns. The study has a pre-test, DMFonF intervention and post-test design. The participants were a teacher, and ten 1st-year and ten 2nd-year kindergarten children. Before the study, children received a meaning-based EFL programme. The children's English development was measured based on PT stages pre- and post-test. Linguistic classroom environments before and during the DMFonF programme were analysed based on the DMFonF feedback categories. Regardless of how long they had been learning English, all the children were at the single-word stage at pre-test. They had all acquired lexical plural at post-test. Most of the children also acquired phrasal plural agreement. Additionally, the linguistic environment was much richer in DMFonF classes than in meaning-based classes.